The Changes Imposed by the COVID-19 Pandemic in Orthopaedics at the HCD: As Mudanças Impostas pela Pandemia COVID-19 no Centro de Ortopedia do HCD - Mineiro, Jorge; Cannas, João; Barroso, Luís; Lança, Nuno; Pedro, João (Gazeta Médica, 2020)
With the novel coronavirus COVID-19 outbreak being highly contagious and spread all over the world, it became clear that health care systems globally would need to evolve, develop strategies, identify new models or rejuvenate old conservative methods of care and thus reduce the risk of disease transmission and be prepared for the worse. In Portugal, both public and private health care systems were together preparing for a disease nobody knew exactly how to handle and the example/scenario we had of its arrival in Europe and progressing west through Italy and Spain was dreadful! In a unique occasion in this country, both private and public health care systems got together to share whatever free beds they had, in particular ICU beds and ventilation facilities taking into account that these were the weakest areas where both the Italian and the Spanish health care systems had failed. [...]